2009
DOI: 10.1007/s00134-009-1724-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and urine neutrophil gelatinase-associated lipocalin in septic versus non-septic acute kidney injury in critical illness

Abstract: Septic AKI patients have higher detectable plasma and urine NGAL compared with non-septic AKI patients. These differences in NGAL values in septic AKI may have diagnostic and clinical relevance as well as pathogenetic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
204
3
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(229 citation statements)
references
References 43 publications
15
204
3
7
Order By: Relevance
“…This is in contrast to the findings reported by Bagshaw and colleagues in this edition of the journal [2] who examined the measurement of both plasma and urinary NGAL in 83 patients with septic and non-septic AKI. Plasma NGAL was determined using the same technique as Cruz et al [3], whereas urinary NGAL was measured by a chemiluminescent microparticle assay using the ARCHITECT platform (Abbott Diagnostics Inc., Abbott Park, IL).…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…This is in contrast to the findings reported by Bagshaw and colleagues in this edition of the journal [2] who examined the measurement of both plasma and urinary NGAL in 83 patients with septic and non-septic AKI. Plasma NGAL was determined using the same technique as Cruz et al [3], whereas urinary NGAL was measured by a chemiluminescent microparticle assay using the ARCHITECT platform (Abbott Diagnostics Inc., Abbott Park, IL).…”
contrasting
confidence: 99%
“…Bagshaw et al [2] found a modest predictive capacity for worsening AKI (AuROC 0.71; 95% CI 0.55-0.88) and for the need of RRT (AuROC 0.70; 95% CI 0.58-0.82). It must be borne in mind that only a small number of patients with AKI did progress (N = 20) or need RRT (N = 13).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They are investigated in different clinical settings including cardiac surgery [10], contrast agent use [11], critically ill patients [12][13][14][15][16][17][18][19][20][21] and in emergency department [22].…”
Section: Introductionmentioning
confidence: 99%